Self-referential and social saliency information influences memory following attention orienting - Zhao, Shuo; Uono, Shota; Hu, Rong Qing; Yoshimura, Sayaka; Toichi, Motomi (Frontiers in Psychology, 2023)
Self-referential information is a processing priority in individuals. Whether or how self-referential information plays a role in attention orienting by modulating memory encoding during attention orienting is presently unknown. First, we investigated this role with self-referential processing for words. Participants were trained to associate two cues (red and green arrows) with social labels (the words “self” and “other” in Experiment 1). Then, participants performed a cueing task to determine whether various targets were presented at a right or left location. Finally, a recognition task of target items was implemented to examine the influence of arrow cues on memory. Second, given that the difference in social salience also exists between self-and other-referential processing, we investigate whether the same effect as the self-referential processing of words exists for emotional faces with high social salience and regardless of emotional valence (a high and a low social salience in Experiment 2A; and a positive and a negative emotional face in Experiment 2B). The results showed that self-referential and emotional cues, irrespective of their emotional valence, enhance memory for the indicated target objects across experiments. This suggests that automatic prioritization of social salience for self-referential words or emotional faces plays an important role in subsequent cognitive processing through attention orienting to influence memory.